2011
DOI: 10.1007/s00044-011-9583-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of antihyperglycemic, α-glucosidase inhibitory, and DPPH free radical scavenging furanochalcones

Abstract: A series of furanochalcone derivatives have been designed and synthesized. Molecular modeling studies were carried out to probe into the mechanism of binding of chalcone inhibitors and understand the structure-activity relationship to identify the contribution of scaffolds and groups in the synthesized analogs to biological activity. The three-dimensional model of a-glucosidase was constructed based on the crystal structure family 31 a-glycosidase (PDB 1XSI) using Modeller9v5. Docking of the inhibitors on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The synthesis of angular 3‐methylfuranochalcones 11 was accomplished from commercially available starting materials in the presence of bases through Claisen–Schmidt condensation (Table ) . First, we investigated the effect of bases on the reactions of 8 with benzaldehyde.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The synthesis of angular 3‐methylfuranochalcones 11 was accomplished from commercially available starting materials in the presence of bases through Claisen–Schmidt condensation (Table ) . First, we investigated the effect of bases on the reactions of 8 with benzaldehyde.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of angular 3-methylfuranochalcones 11 was accomplished from commerciallya vailables tarting materials in the presence of bases through Claisen-Schmidt condensation ( Table 2). [14] First, we investigated the effect of bases on the reactions of 8 with benzaldehyde.I tw as found that 5equivalents of NaOH can hardly catalyzet he reaction (yield < 5%). KOH gave 57 %y ield of the desired product 11 a.F urther screening of other bases afforded av ery good yield (82 %) of 11 a,a nd NaH was proved to be optimal for this transformation.…”
Section: Synthesis Of Angular 3-methylfuranochalcones(11)mentioning
confidence: 99%
See 2 more Smart Citations